Study of Determining Water Quality Status and Water Distribution Using Five Methods in Selorejo Reservoir. - Mochamad Fikri Dwi Putra; Rini Wahyu Sayekti; Moh. Sholichin (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
A reservoir is a place to store river water formed by the construction of a dam. The main problem of reduced water quality for Selorejo Reservoir is caused by the inflow of water from livestock, agricultural, and household wastes containing high amounts of nitrates and phosphates. The objective of this study is to determine the water quality status of Selorejo Reservoir using the DOE-WQI, Pollution Index, DWQI, Ved Prakash Index, and Prati Index methods; to find out the distribution of characteristics for water quality status using the IDW method and to find out the capacity of water pollution load for Selorejo Reservoir using Total-P. The research showed that the characteristics of water contamination for Selorejo Reservoir in 6 years indicate light pollution. Through the DWQI method, the contamination percentage became smaller downstream, while the DOE-WQI, Pollution Index, Ved Prakash Index, and Prati Index methods showed the opposite results. Total-P levels in the 2021 dry season were 42.475 mg/m3 (upstream), 35.767 mg/m3 (middle), and 37.567 mg/m3 (downstream). The pollution load capacity is 71.77 mg/m3 (upstream), 80.14 mg/m3 (middle), and 77.9 mg/m3 (downstream). It can thus be said that Selorejo Reservoir is still within the maximum reservoir pollution load limit.